Developing student social attitude self-assessment instruments: A study in vocational high school - Nurrahman, Arief; Sukirno, Sukirno; Pratiwi, Dwi Setyo; Iskandar, Joni; Rahim, Abdul; Rahmaini, Indah Sari (REID (Research and Evaluation in Education), 2022)
This study aims to develop a self-assessment instrument in the affective domain of students' social attitudes, which was modified by the case of the instrument item. The measurement results can be used as a recommendation for the self-assessment of students' social attitudes at school. The sampling technique used is cluster random sampling. The instrument was content validated by five experts using Aiken, and construct validation using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA), while the reliability estimation used Cronbach's Alpha coefficient. The results showed that there were seven instrument factors to assess the affective domain of students' social attitudes, namely honest, disciplined, polite, caring, responsible, responsive, and proactive. Content validity using the Aiken index shows 28 valid items. The construct validity of the instrument was carried out using EFA with a KMO value of 0.618, which means it has met the requirements. The fit model based on the CFA results shows the Chi-square value <2df = 258.02<2x341, p-value = 0.416>0.05, RMSEA = 0.0197<0.08, CFI = 0.91, GFI = 0.86, AGFI = 0.88.  In item estimation, the factor loading value is > 0.3, which means the items in the instrument are valid. The estimated reliability of the instrument shows the Cronbach Alpha coefficient value of 0.895, which means that all developed instruments are reliable. Valid and reliable instruments are very important to get good information about the affective assessment of students' social attitudes.